Social security data for posting of workers: Reform of cross-border coordination of social security - Anneliese Kärcher; Manfred Walser (Hans-Böckler-Stiftung, 2023)
The cross-border exchange of social security data in the case of postings requires reforms both in European social security coordination law and at national level. Digitalised and simplified procedures employing modern technologies, improvements around the PD A1, better identification of the parties involved and other reform proposals would not only relieve companies from red tape and strengthen the European Internal Market, but also significantly increase the social protection of workers.
Keywords: 330